Impacts of changing ocean conditions on American plaice (Hippoglossoides platessoides) stock dynamics - Jamie T. Behan; Lisa A. Kerr (Environmental Biology of Fishes, 2026)
` Temperatures in the Gulf of Maine have increased over the past four decades and are influencing key biological processes of marine fishes. We examined relationships between key aspects of American plaice ( Hippoglossoides platessoides ) stock dynamics (i.e., recruitment, distribution, and growth) and environmental variables to explore the effects of changing ocean conditions. Time series of relevant environmental variables included sea surface (SST) and bottom temperature anomalies, Atlantic Multidecadal Oscillation (AMO), North Atlantic Oscillation (NAO), and Gulf Stream Index (GSI). Spawning stock biomass (SSB) was included in some models to represent density dependence. Generalized additive models (GAMs) were used to evaluate relationships between these independent variables and stock dynamics over time. Recruitment analyses (age 1 abundance and R/SSB) revealed significant relationships with AMO, suggesting positive recruitment under colder and slightly warmer than average regional SST conditions. Distribution shifts in mean depth and latitude were mostly significantly and positively related to NAO, bottom temperature anomaly, and SSB, indicating movement into deeper and more northerly waters with warming and increasing biomass. Growth analyses (weight at age and condition index) revealed a significant negative relationship with AMO, suggesting decreasing somatic growth with increasing AMO values (North Atlantic-wide SST). SSB and bottom temperature anomaly also exhibited a significant positive relationship with weight at age, suggesting increased somatic growth with increasing SSB and bottom temperature. These analyses demonstrate the likelihood that changing ocean conditions are influencing American plaice stock dynamics and could be used to inform climate-integrated stock assessment modeling for American plaice.

Climate Attribution in Fishery Stock Assessment: Case Studies From the Northeast U.S. Groundfish Stocks - Lisa A. Kerr; Jamie T. Behan; Steven X. Cadrin; Alexander C. Hansell; Amanda R. Hart; Jessica A. Kittel; Scott I. Large; Timothy J. Miller; Abigail S. Tyrell (Fish and Fisheries, 2026)
Climate change poses an unprecedented risk to fisheries ecosystems and economies globally. Ocean warming has led to observed geographic shifts and changes in the productivity of fish stocks. Due to the rapid pace of change in many of the world's oceans, there is a critical need to develop and apply scientific knowledge and tools that can help account for non‐stationarity and integrate climate and ecosystem drivers into fishery stock assessment to improve management outcomes. We developed a structured approach to identify and integrate the impact of climate and ecosystem change on fish stock dynamics in the context of stock assessment processes. We describe lessons learned in the application of this approach to groundfish stock assessment processes in the Northeast U.S. (American plaice, Atlantic cod and yellowtail flounder). The approach involves three general steps: (1) synthesizing the state of knowledge on stock‐climate relationships, (2) accounting for climate impacts on key data inputs and biological parameters that inform assessments, and (3) developing and evaluating the performance of climate informed stock assessment models. This approach represents an advance in climate attribution within stock assessment and is expected to enhance assessment performance and projection realism, supporting fisheries decision‐making for future resource sustainability.

Diet composition of data‐limited marlins ( Istiophoridae ) in the Northwest Atlantic - Joseph J. Dello Russo; John M. Logan; Riley Austin; Zachary T. Whitener; Isabelle Sée; Benjamin M. Hurley; Lisa A. Kerr; Joseph M. Quattro; Walter J. Golet (Journal of Fish Biology, 2026)
Knowledge of the dietary composition of Atlantic marlins, especially for recently acknowledged species such as roundscale spearfish ( Tetrapturus georgii ), is limited, as sample access is constrained by international quotas and intermittent landing rates. A series of annual offshore recreational fishing tournaments target Atlantic blue marlin ( Makaira nigricans ), white marlin ( Kajikia albida ) and roundscale spearfish on their seasonal foraging grounds in the South and Mid‐Atlantic Bight. Through this network of tournaments and recreational anglers, we collected stomachs from Atlantic blue marlin ( n = 32), white marlin ( n = 35) and roundscale spearfish ( n = 44) from 2018 to 2020 to investigate general diet composition. Stomach content analysis and DNA barcoding identified a total of 16 prey families across the three focal species, but the majority of prey weight (%W) was from two families (Scombridae and Ommastrephidae). Blue marlin and roundscale spearfish were predominantly piscivorous (99.0 and 80.6%W fishes, respectively), whereas white marlin mainly consumed cephalopods (80%W). The contribution of Scombridae was highest for blue marlin (94.6%W), intermediate for roundscale spearfish (51.7%W) and lowest for white marlin (11%W), with an inverse pattern of relative contribution for Ommastrephidae (0.9, 16.1 and 73.9%W, respectively). Roundscale spearfish and white marlin, despite having a near identical morphology, had diets composed of different prey types in our sample. These dietary data, from three epipelagic apex predators, provide important information for wider ecosystem‐based studies, including in relation to the Mackerel, Squid and Butterfish Fishery Management Plan overseen by the Mid‐Atlantic Fishery Management Council.

Assessing efficacy in MPA design decisions using a bespoke and interactive fisheries management tool - Oliver T. Hogg; Matthew Kerr; Lenka Fronkova; Roi Martinez; William Procter; Lisa Readdy; Christopher Darby (Biological Conservation, 2024)

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

Consequences of ignoring climate impacts on New England groundfish stock assessment and management - Mackenzie D. Mazur; Jerelle Jesse; Steven X. Cadrin; Samuel B. Truesdell; Lisa Kerr (Fisheries Research, 2023)

Implications of fisheries allocation policy on anticipated climate change impacts - Kanae Tokunaga; Lisa A. Kerr; Andrew J. Pershing (Marine Policy, 2023)

Damselfish Embryos as a Bioindicator for Military Contamination on Coral Reefs at Johnston Atoll, Pacific Ocean - Lisa Kerr Lobel; Phillip S. Lobel (Fishes, 2022)
This study investigated the association between sediment contamination, PCB accumulation in adult nesting males and the occurrence of embryonic abnormalities in the damselfish, Abudefduf sordidus, from two sites with high PCB contamination and three “reference” sites (contaminants very low or not measurable) within Johnston Atoll, Central Pacific Ocean. Developmental abnormalities were assessed in damselfish embryos collected in the field during four natural spawning seasons (1996, 1998, 1999, and 2001). Laboratory incubations of abnormal embryos demonstrated that the observed abnormalities were lethal. PCBs were measured in fish collected in three years. Mean whole-body concentrations of total PCBs ranged from 364.6 to 138,032.5 ng/g lipid. A significant residue–effect relationship was found between total PCB concentration and embryo abnormalities. The occurrence of embryo abnormalities was positively related to fish PCB concentration (other contaminants were also evaluated including metals and dioxins). This study demonstrates the utility of using damselfish embryos as a bioindicator tool for monitoring coral reefs. It also provides baseline-monitoring criteria and evaluates sediment quality benchmarks used for ecological risk assessments on coral reefs.

A Genetic Assessment of Parentage in the Blackspot Sergeant Damselfish, Abudefduf sordidus (Pisces: Pomacentridae) - Lisa Kerr Lobel; Devin M. Drown; Paul H. Barber; Phillip S. Lobel (Fishes, 2019)
Microsatellite markers were used to investigate the reproductive behavior of the damselfish Abudefduf sordidus at Johnston Atoll, Central Pacific Ocean. Genetic results indicated that ten males maintained guardianship over their nest territories for up to nine nest cycles during a 3.5 month period. Genotypes of 1025 offspring sampled from 68 nests (composed of 129 clutches) were consistent with 95% of the offspring being sired by the guardian male. Offspring lacking paternal alleles at two or more loci were found in 19 clutches, indicating that reproductive parasitism and subsequent alloparental care occurred. Reconstructed maternal genotypes allowed the identification of a minimum of 74 different females that spawned with these ten territorial males. Males were polygynous, mating with multiple females within and between cycles. Genetic data from nests, which consisted of up to four clutches during a reproductive cycle, indicated that each clutch usually had only one maternal contributor and that different clutches each had different dams. Females displayed sequential polyandry spawning with one male within a cycle but switched males in subsequent spawning cycles. These results highlight new findings regarding male parasitic spawning, polygyny, and sequential polyandry in a marine fish with exclusive male paternal care.

Modeling marine pelagic fish species spatiotemporal distributions utilizing a maximum entropy approach - Lifei Wang; Lisa A. Kerr; Nicholas R. Record; Eric Bridger; Benjamin Tupper; Katherine E. Mills; Edward M. Armstrong; Andrew J. Pershing (Fisheries Oceanography, 2018)
Understanding how ocean conditions influence fish distributions is critical for elucidating the role of climate in ecosystem change and forecasting how fish may be distributed in the future. Traditional species distribution models are often applied to scientific‐survey data, which include species presence‐absence information, to predict distributions. Maximum entropy (MaxEnt) models are promising tools as they can be applied to presence‐only data (e.g., data collected from fishermen targeting a specific species or from observers in citizen‐science programs). We used MaxEnt models to relate occurrence records of three marine pelagic fish (Atlantic herring, Atlantic mackerel, and butterfish) in fishery‐dependent data to environmental conditions (sea surface temperature ( SST ) and chlorophyll‐ a concentration from satellite remote sensing, bathymetry, and climate indices), and evaluated model performance by both cross‐validation and validation using fishery‐independent data. We developed monthly habitat suitability maps for these fish in the Northwest Atlantic Shelf area, and assessed the relative influence of environmental factors on their distributions. Across months, their suitable habitat areas varied with each species exhibiting inshore‐offshore and north‐south movements in response to changing environmental conditions. Overall, SST and chlorophyll‐ a concentration had the greatest influence on the distributions of these fish, with bathymetry having moderate influence and climate indices having little influence. Our application of MaxEnt models enabled us to integrate presence‐only data and high resolution environmental data from satellite remote sensing to describe spatiotemporal distributions of marine pelagic fish. These models were used to hindcast species occurrence in relation to historical environmental conditions to evaluate their predictive performance, and have the potential to provide nowcasts in relation to current conditions or forecasts of species future distributions.

Using bomb radiocarbon to estimate age and growth of the white shark, Carcharodon carcharias, from the southwestern Indian Ocean - Heather M. Christiansen; Steven E. Campana; Aaron T. Fisk; Geremy Cliff; Sabine P. Wintner; Sheldon F. J. Dudley; Lisa A. Kerr; Nigel E. Hussey (Marine Biology, 2016)

Validated age estimates for large white sharks of the northeastern Pacific Ocean: altered perceptions of vertebral growth shed light on complicated bomb Δ14C results - Allen H. Andrews; Lisa A. Kerr (Environmental Biology of Fishes, 2015)

Partial Migration Across Populations of White Perch (Morone americana): A Flexible Life History Strategy in a Variable Estuarine Environment - Lisa A. Kerr; David H. Secor (Estuaries and Coasts, 2012)

Latent effects of early life history on partial migration for an estuarine-dependent fish - Lisa A. Kerr; David H. Secor (Environmental Biology of Fishes, 2010)

Derivation of Man-1 and Man-2 research grade human embryonic stem cell lines - Maria V. Camarasa; Robbie W. Kerr; Sharon F. Sneddon; Nicola Bates; Lisa Shaw; Rachel A. Oldershaw; Fiona Small; Melissa A. Baxter; Tristan R. Mckay; Daniel R. Brison; Susan J. Kimber (In Vitro Cellular & Developmental Biology - Animal, 2010)

Investigations of Δ 14C, δ 13C, and δ 15N in vertebrae of white shark (Carcharodon carcharias) from the eastern North Pacific Ocean - Lisa A. Kerr; Allen H. Andrews; Gregor M. Cailliet; Thomas A. Brown; Kenneth H. Coale (Environmental Biology of Fishes, 2006)

Application of bomb radiocarbon chronologies to shortfin mako (Isurus oxyrinchus) age validation - Daniele Ardizzone; Gregor M. Cailliet; Lisa J. Natanson; Allen H. Andrews; Lisa A. Kerr; Thomas A. Brown (Environmental Biology of Fishes, 2006)